Philosophical Values of The Characters Kudu Lempang and Panangan in Wayang Sukuraga - Saskia, Delsa (PT. Alahyan Publisher Sukabumi, 2023)
Wayang is a traditional Indonesian art that has existed for a long time. In the art of wayang, there are philosophical values contained both in the puppet characters and in the story. Therefore, this study aims to discuss the philosophical values contained in the sukuraga puppet characters. Where in this study the characters to be discussed are the Kudu Lempang and Panangan characters. This research uses qualitative research methods using qualitative analysis, data collection used by interview. In this study there are 2 philosophical values contained in the kudu lempang and panangan characters. The philosophical value of wayang dukurahs is more centered on how humans should use their limbs in accordance with their nature as God's creation.